Quorum Sensing N-acyl Homoserine Lactones-SdiA Suppresses Escherichia coli-Pseudomonas aeruginosa Conjugation through Inhibiting traI Expression - Lu, Yang; Zeng, Jianming; Wu, Binning; E, Shunmei; Wang, Lina; Cai, Renxin; Zhang, Ni; Li, Youqiang; Huang, Xianzhang; Huang, Bin; Chen, Cha (Frontiers in Cellular and Infection Microbiology, 2017)
Conjugation is a key mechanism for horizontal gene transfer and plays an important role in bacterial evolution, especially with respect to antibiotic resistance. However, little is known about the role of donor and recipient cells in regulation of conjugation. Here, using an Escherichia coli (SM10λπ)-Pseudomonas aeruginosa (PAO1) conjugation model, we demonstrated that deficiency of lasI/rhlI, genes associated with generation of the quorum sensing signals N-acyl homoserine lactones (AHLs) in PAO1, or deletion of the AHLs receptor SdiA in the donor SM10λπ both facilitated conjugation. When using another AHLs-non-producing E. coli strain EC600 as recipient cells, deficiency of sdiA in donor SM10λπ hardly affect the conjugation. More importantly, in the presence of exogenous AHLs, the conjugation efficiency between SMλπ and EC600 was dramatically decreased, while deficiency of sdiA in SMλπ attenuated AHLs-inhibited conjugation. These data suggest the conjugation suppression function of AHLs-SdiA chemical signaling. Further bioinformatics analysis, β-galactosidase reporter system and electrophoretic mobility shift assays characterized the binding site of SdiA on the promoter region of traI gene. Furthermore, deletion of lasI/rhlI or sdiA promoted traI mRNA expression in SM10λπ and PAO1 co-culture system, which was abrogated by AHLs. Collectively, our results provide new insight into an important contribution of quorum sensing system AHLs-SdiA to the networks that regulate conjugation.